FAM83 family oncogenes are broadly involved in human cancers: an integrative multi‐omics approach. Issue 2 (9th January 2017) - Snijders, Antoine M.; Lee, Sun‐Young; Hang, Bo; Hao, Wenshan; Bissell, Mina J.; Mao, Jian‐Hua
Abstract : The development of novel targeted therapies for cancer treatment requires identification of reliable targets. FAM83 ('family with sequence similarity 83') family members A, B, and D were shown recently to have oncogenic potential. However, the overall oncogenic abilities of FAM83 family genes remain largely unknown. Here, we used a systematic and integrative genomics approach to investigate oncogenic properties of the entire FAM83 family members. We assessed transcriptional expression patterns of eight FAM83 family genes (FAM83A‐H) across tumor types, the relationship between their expression and changes in DNA copy number, and the association with patient survival. By comparing the gene expression levels of FAM83 family members in cancers from 17 different tumor types with those in their corresponding normal tissues, we identified consistent upregulation of FAM83D and FAM83H across the majority of tumor types, which is largely driven by increased DNA copy number. Importantly, we found also that a higher expression level of a signature of FAM83 family members was associated with poor prognosis in a number of human cancers. In breast cancer, we found that alterations in FAM83 family genes correlated significantly with TP53 mutation, whereas significant, but inverse correlation was observed with PIK3CA and CDH1 (E‐cadherin) mutations. We also identified that expression levels of 55 proteins were significantly associated with alterations in FAM83 family genes including a decrease in GATA3, ESR1, and PGR proteins in tumors with alterations in FAM83. Our results provide strong evidence for a critical role of FAM83 family genes in tumor development, with possible relevance for therapeutic target development. Abstract : Transcriptional levels of FAM83 family members are frequently and dramatically elevated across human tumor types. Using a systemic and integrative genomics approach, we found that increased expression of FAM83 genes is largely driven by increased DNA copy number. The FAM83 family gene signature is associated with poor survival across human tumor types and FAM83 gene alterations are significantly correlated with TP53, PIK3CA, and E‐cadherin mutations.